INNOVATIVE TECHNOLOGIES OF PATRIOTIC EDUCATION - Lyudmila P. Gulyanova; Olga V. Nepsha (Высшее образование в России, 2016)
The article is devoted to innovative technologies of patriotic education, developed on the base of the humanization of education theory and introduced in the International Innovative University. The authors analyze the role of the Association of scientific, technical and creative intellectuals created by the University in patriotic education. There are also considered the innovative forms of tutorial work such as the journal «Patriot: our time» published by the University, website «Fatherland».